Biological and molecular diagnostic methods in breast cancer Part I. Markers, genomics and proteomics - Ślubowski, Tadeusz; Ślubowska, Małgorzata; Kujawa, Marek (Contemporary Oncology/Współczesna Onkologia, 2007)
The review on breast cancer biological and molecular diagnostics discusses up-to-date knowledge on quantitative and qualitative biological markers, identifiable either in cells and/or in bodily fluids. It deals with identification of genes and corresponding proteins as well as compounds that might be recognized through laboratory techniques fallowing for same time evaluation of thousands of biological and chemical traits displaying potential as breast cancer markers. It also overviews changes in cell growth, cell cycle disturbances, apoptosis, cell adhesion and mobility as well as an improper gene expression. It also describes cancer cell genome markers related to DNA repairing leading to loss or breakage of chromosomes, gene amplification thus increasing risk and/or a high level of malignancy. It also outlines information on intracellular signaling networks playing an important role in growth, differentiation and cell death as well as serum biomarkers such as: CA15-3, protein, carcinoembryonic antigen (CEA), cytokeratins (TPA, TPS a Cyfra 21.1).